PLASMA KINETIC MEASUREMENTS USING TIME-RESOLVED ACTINOMETRY - COMPARISONS WITH LASER-INDUCED FLUORESCENCE - Hancock, G; Sucksmith, J; Toogood, M (1990)
Optical diagnostics have been used to study the steady-state concentrations and kinetics of reactive species in CF4 and CF4/O2 plasmas. The CF2 radical was studied by two techniques, laser-induced fluorescence (LIF) and optical emission, in order to test the validity of using the latter method as a way of determining relative changes in concentration of the ground-state radical. Both techniques were first used under steady-state conditions and then for measurements of time-resolved behavior following plasma extinction. For the optical emission studies a new method, time-resolved actinometry, was developed. The kinetics of F atoms, which cannot conveniently be measured by other methods such as LIF, were then studied by this technique, under a variety of conditions and in the presence and absence of Si surfaces. © 1990 American Chemical Society.